Employee brand equity and brand empowerment in Islamic banking: Mediating role of brand psychological ownership - Mohd Mokhtar, Sany Sanuri; Altaf, Mohsin; Abd Ghani, Noor Hasmini (2018)
The intention of the research is to explore the mediating role of brand psychological ownership (BPO) in the association between brand empowerment (BEm) and employee brand equity (EBE) of the employees of Islamic banks. For the reason, the data were collected from the 274 employees working in Islamic banks through multi-stage probability sampling. Results of the study revealed that the direct connection of BEm with EBE is non-supportive. On the other hand, the indirect connection of BEm with EBE through BPO is supportive in Islamic banking.